2020
DOI: 10.1111/iju.14228
|View full text |Cite
|
Sign up to set email alerts
|

Complete puborectalis, puboperinealis muscle and urethral rhabdomyosphincter preservation in laparoscopic radical prostatectomy: Anatomical landmarks to achieve early urinary continence

Abstract: Abbreviations & Acronyms AFMS = anterior fibromuscular stroma BCR = biochemical recurrence BMI = body mass index CZ = central zone DPPM = dissection of puboperinealis and puborectalis muscle DVP = dorsal vein complex of the penis ECE = extracapsular extension EUS = external urethral sphincter ICIQ-SF = International Consultation on Incontinence Questionnaire Short-Form IQR = interquartile range IUS = internal urethral sphincter LRP = laparoscopic radical prostatectomy MRI = magnetic resonance imaging MsPP = pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…However, many of these parameters are composed of skeletal measurements alone 11 , 12 , although the pelvic cavity is composed of not only the pelvic bone structure but also the pelvic muscles, fat, and other soft tissue that lie above the bony structure. The musculature is highly important when discussing outcomes of RP, as reflected in studies where preservation of the levator ani muscle is reported to benefit early urinary continence recovery after RP 13 . Accordingly, measurements reflecting the size of the pelvic cavity should contain elements regarding this muscle in addition to the bony structure.…”
Section: Discussionmentioning
confidence: 99%
“…However, many of these parameters are composed of skeletal measurements alone 11 , 12 , although the pelvic cavity is composed of not only the pelvic bone structure but also the pelvic muscles, fat, and other soft tissue that lie above the bony structure. The musculature is highly important when discussing outcomes of RP, as reflected in studies where preservation of the levator ani muscle is reported to benefit early urinary continence recovery after RP 13 . Accordingly, measurements reflecting the size of the pelvic cavity should contain elements regarding this muscle in addition to the bony structure.…”
Section: Discussionmentioning
confidence: 99%
“…From the inner layers are the urethral striated sphincter, the urethral smooth sphincter (circular fibers), and the urethral smooth sphincter (longitudinal fibers). The puboperineal muscle, the puborectal muscle, and the pubococcygeus muscle also support and surround the urethra [7]. Preservation of the nerves including the pudendal and pelvic nerves also contribute to urinary continence after RARP.…”
Section: Discussionmentioning
confidence: 99%
“…The puboperinealis muscle originates from the body of the pubis and courses posteriorly to attach the dorsal medium raphe. The pubococcygeus muscle originates from the body of the pubis and courses posteriorly to attach along the midline as far back as the coccyx [7].…”
Section: Classification Of Pelvic Floor Muscle Injurymentioning
confidence: 99%
“…17 The preservation of anatomical structures, such as the endopelvic fascia, the detrusor apron nerve through intrafascial dissecting, and suitable length of urethral membrane contributed to early recovery of urinary continence. 18 It was shown that nerve-preserving bilateral processes can retain the function of motor control of the urethral sphincter, thereby improving postoperative urinary control. 19 The detrusor apron, extended from the bladder's interior wall with direct continuity of pubis, had aroused widespread concern recently.…”
Section: Discussionmentioning
confidence: 99%